Chemical abundances of globular clusters in NGC 5128 (Centaurus A). Issue 4 (27th February 2018) - Hernandez, Svea; Larsen, Søren; Trager, Scott; Kaper, Lex; Groot, Paul
Abstract: We perform a detailed abundance analysis on integrated-light spectra of 20 globular clusters (GCs) in the early-type galaxy NGC 5128 (Centaurus A). The GCs were observed with X-Shooter on the Very Large Telescope (VLT). The cluster sample spans a metallicity range of −1.92 < [Fe/H] < −0.13 dex. Using theoretical isochrones, we compute synthetic integrated-light spectra and iterate the individual abundances until the best fit to the observations is obtained. We measured abundances of Mg, Ca, and Ti, and find a slightly higher enhancement in NGC 5128 GCs with metallicities [Fe/H] < −0.75 dex, of the order of ∼0.1 dex, than in the average values observed in the Milky Way (MW) for GCs of the same metallicity. If this α-enhancement in the metal-poor GCs in NGC 5128 is genuine, it could hint at a chemical enrichment history different than that experienced by the MW. We also measure Na abundances in 9 out of 20 GCs. We find evidence for intracluster abundance variations in six of these clusters where we see enhanced [Na/Fe] > +0.25 dex. We obtain the first abundance measurements of Cr, Mn, and Ni for a sample of the GC population in NGC 5128 and find consistency with the overall trends observed in the MW, with a slight enhancement (<0.1 dex) in the Fe-peak abundances measured in the NGC 5128.